Changes in Angiotensin Receptor Distribution and in Aortic Morphology Are Associated with Blood Pressure Control in Aged Metabolic Syndrome Rats - Verónica Guarner-Lans; Elizabeth Soria-Castro; Rocío Torrico-Lavayen; Araceli Patrón-Soberano; Karla G. Carvajal-Aguilera; Vicente Castrejón-Tellez; María Esther Rubio-Ruiz (International Journal of Hypertension)
The role of the renin-angiotensin system (RAS) in blood pressure regulation in MS during aging is unknown. It participates in metabolic syndrome (MS) and aging regulating vascular tone and remodeling. RAS might participate in a compensatory mechanism decreasing blood pressure and allowing MS rats to reach 18 months of age and it might form part of therapeutical procedures to ameliorate MS. We studied histological changes and distribution of RAS receptors in aortas of MS aged rats. Electron microscopy images showed premature aging in MS since the increased fibrosis, enlarged endothelium, and invasion of this layer by muscle cells that was present in control 18-month-old aortas were also found in 6-month-old aortas from MS rats. AT1, AT2, and Mas receptors mediate the effects of Ang II and Ang 1-7, respectively. Fluorescence from AT2 decreased with age in control and MS aortas, while fluorescence of AT1 increased in aortas from MS rats at 6 months and diminished during aging. Mas expression increased in MS rats and remained unchanged in control rats. In conclusion, there is premature aging in the aortas from MS rats and the elevated expression of Mas receptor might contribute to decrease blood pressure during aging in MS.